Decreased expression of acetyl‐CoA synthase 2 promotes metastasis and predicts poor prognosis in hepatocellular carcinoma. Issue 7 (20th May 2017) - Sun, Lin; Kong, Yinlong; Cao, Manqing; Zhou, Hongyuan; Li, Huikai; Cui, Yunlong; Fang, Feng; Zhang, Wei; Li, Jiafeng; Zhu, Xiaolin; Li, Qiang; Song, Tianqiang; et al.
Abstract : Metastasis is a serious risk that may occur during the treatment of hepatocellular carcinoma (HCC), preventing many patients from being surgical candidates and contributing to poor prognosis. Hypoxia has been proved an important factor of metastasis through the epithelial–mesenchymal transition (EMT) pathway. Acetyl‐CoA synthase 2 (ACSS2) provides an acetyl group for the acetylation of hypoxia‐inducible factor (HIF)‐2α, and this epigenetic modification affects the activity of HIF‐2α and the subsequent EMT process. Here, we showed that ACSS2 expression was negatively correlated with HCC malignancy. Knockdown of ACSS2 increased the invasion and migration ability of HCC cells and promoted EMT without increasing the total protein level of HIF‐2α, even in hypoxic conditions. The immunoprecipitation assay revealed downregulated acetylation levels of HIF‐2α after ACSS2 knockdown in hypoxic conditions, which resulted in enhanced HIF‐2α activity. Finally, decreased expression of ACSS2 was found to be related to advanced stage and poor overall survival and disease‐free survival rates in a cohort of patients with HCC. In conclusion, ACSS2 plays an important role in the acetylation process of HIF‐2α, which effectively modifies the activity of HIF‐2α under hypoxic conditions and greatly impacts on the prognosis of patients with HCC. Abstract : Decreased expression of ACSS2 leads to HIF‐2α deacetylation, which enhances the activity of HIF‐2α in hypoxic conditions and subsequently increases metastasis and results in poor prognosis.